2023
DOI: 10.1080/15502783.2023.2178858
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate-Protein drink is effective for restoring endurance capacity in masters class athletes after a two-Hour recovery

Abstract: Background Carbohydrate (CHO) and carbohydrate-protein co-ingestion (CHO-P) have been shown to be equally effective for enhancing glycogen resynthesis and subsequent same-day performance when CHO intake is suboptimal (≤0.8 g/kg). Few studies have specifically examined the effect of isocaloric CHO vs CHO-P consumption on subsequent high-intensity aerobic performance with limited time to recover (≤2 hours) in masters class endurance athletes. Methods This was a randomized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The relative dosage of 1.2 g of CHO/kg/h was used for the CHO beverage intake [1] and was given to the participants along with the granola bars during the final three hours of the recovery period. In contrast, a cycling trial in master endurance athletes by Goldstein et al (2023) [42] compared beverages given in relative rates of CHO (1.2 g/kg) and CHO + protein (0.8 g/kg of CHO + 0.4 g/kg of protein) in a repeat exercise situation and found that both the CHO and CHO + protein conditions resulted in significantly longer test-to-exhaustion times than the placebo condition of electrolytes + water. In this study, no other supplements besides the experimental beverages were given during the 2 h recovery period that occurred between the two exercise bouts [42].…”
Section: Discussionmentioning
confidence: 99%
“…The relative dosage of 1.2 g of CHO/kg/h was used for the CHO beverage intake [1] and was given to the participants along with the granola bars during the final three hours of the recovery period. In contrast, a cycling trial in master endurance athletes by Goldstein et al (2023) [42] compared beverages given in relative rates of CHO (1.2 g/kg) and CHO + protein (0.8 g/kg of CHO + 0.4 g/kg of protein) in a repeat exercise situation and found that both the CHO and CHO + protein conditions resulted in significantly longer test-to-exhaustion times than the placebo condition of electrolytes + water. In this study, no other supplements besides the experimental beverages were given during the 2 h recovery period that occurred between the two exercise bouts [42].…”
Section: Discussionmentioning
confidence: 99%
“…Glycogen replenishment [69], reduction of exercise induced skeletal muscle damage [40], enhanced performance in subsequent efforts [27] Immediate: 2 Prolonged: 1.5 Delayed: not confirmed There is the strongest evidence for carbohydrates and protein efficiency; emerging evidence suggests that for example vitamin D, omega-3 polyunsaturated fatty acids, creatine, and collagen/vitamin C are potentially beneficial In the SYRN concept, considering the need for an individualized approach to the athletes, it adapts the recovery actions to their own needs and preferences. Thus, the athlete's task is to follow the scheme of evaluation of the training RPE and consider whether the undertaken recovery protocol is sufficient to ensure proper regeneration (Fig.…”
Section: Napsmentioning
confidence: 99%
“…For example, the addition of carbohydrates (~35 g) to amino acids (~6 g of a balanced amino acid mixture) has been shown to produce a net muscle protein synthetic response that was roughly equivalent to the sum of the independent effect of either nutrient in isolation [18], suggesting there may be synergistic benefits of combining protein and carbohydrates together. These benefits appear to extend to master's athletes (≥35 years) as well as the consumption of carbohydrates and carbohydrates + protein after intense endurance exercise elevated performance to a greater degree than supplementing with water + electrolytes [19]. However, the specific influence of such nutritional interventions on occupational performance in firefighters is currently unknown.…”
Section: Introductionmentioning
confidence: 99%